Introducing improvements in the mass rearing of the housefly: biological, morphometric and genetic characterization of laboratory strains. Issue 4 (August 2014) - Pastor, B.; Martínez-Sánchez, A.S.; Ståhls, G.A.; Rojo, S.
Abstract Understanding the biology of the housefly (Musca domestica L.) is crucial for the development of mass-rearing protocols in order to use this insect as a degradation agent for livestock waste. In this study, the biological and genetic differences between different laboratory strains of M. domestica were analysed. Additionally, hybrids were obtained by mixing the strains and their biological parameters were also measured. The three strains of M. domestica presented differences in their biological and morphological parameters, the main differences were: size, egg production and developmental time. The strain A (specimens from Central Europe) had the best qualities to be used in mass-rearing conditions: it produced the largest quantities of eggs (5.77±0.38 eggs per female per day), the individuals were larger (12.62±0.22 mg) and its developmental time was shorter (15.22±0.21 days). However, the strain C (specimens from SW Europe) produced the fewest eggs (3.15±0.42 eggs per female per day) and needed 18.16±0.49 days to develop from larva to adult, whilst the females from strain B (from South America) produced 4.25±0.47 eggs per day and needed 17.11±0.36 days to complete its development. Genetic analysis of the original laboratory strains showed four different mtDNA cytochrome c oxidase subunit I haplotypes. Statistical parsimony network analysis showed that the SW Europe and South-American strains shared haplotypes, whereas the Central Europe strain did not. Upon hybridizing the strains, variations in egg production and in developmental time were observed in between hybrids and pure strains, and when mixing Central European and South-American strains only males were obtained.